Synthesis, optical linear and non-linear characterization and metal ion sensing application of some novel thieno[2,3-b]thiophene-2,5-dicarbohydrazide Schiff base derivatives - Ahmed. M. M. Soliman; Mahmoud Abd El Aleem Ali Ali El-Remaily; Moumen S. Kamel; Alaa El-Araby; E. Kh. Shokr (Scientific Reports)
Abstract Synthesized 3,4-Diaminothieno[2,3-b]thiophene-2,5-dicarbohydrazide (DTT) Schiff base derivatives newly were synthesized by attaching with different aldehydes, deposited in thin film form by thermal evaporation technique, and characterized by UV–Visible-NIR spectroscopy, FT-IR, NMR, and elemental analysis. It is revealed that compound 4 has the highest absorption peak intensity at 586 nm. The allied absorption, dielectric, and dispersion parameters have been calculated and discussed. The obtained results manifested that compound 4 and DTT have lower (1.92 eV), and higher (3.47 eV) energy band gap values, respectively, as a result of the conjugation number effect. The high nonlinear refractive index n2 and third-order nonlinear susceptibility χ(3) of these organic thin films are comparable with those of chalcogenide and oxide materials, making them promising for nonlinear optical systems. Compound 4 displays high sensitivity towards metal ion detection (ex. Cu+2, Ni+2, Fe+3, Mn+2, Pb+2, Co+2), suggesting its ability to be applied as a metal ion sensor and quantifying their concentration levels by means of a suitable calibration curve.